Sinur Ma Pinahan Gabe Na Niula - Sibarani, Daniel Parsaoran (Educatio Christi, 2024)
The Batak philosophy "Sinur ma pinahan gabe na niula" reflects the deep integration between economics and ecology. This philosophy contains local wisdom that is relevant in answering the challenges of modern agriculture. Through organic farming, this philosophy offers sustainable solutions by optimizing the potential of nature and paying attention to the welfare of farmers. "Sinur ma pinahan gabe na niula" emphasizes the importance of balancing ecological sustainability and economic benefits. This study analyzes the philosophy of "Sinur ma pinahan gabe na niula" in the context of organic farming systems, connecting local wisdom with the theory of bioregionalism and sustainable entrepreneurship. The revitalization of this philosophy is expected to encourage public awareness of the importance of economic and ecological integration for a sustainable future.